The effects of the implementation of value-based management - Valentin Beck (International Journal of Economic Sciences and Applied Research, 2014)
Many managers are caught in a dilemma: between a desire to maximize the value of their companies and the demands of "stakeholder theory" to take into account the interests of all the stakeholders in a firm. The way out of the conflict lies in a new way of measuring value. The purpose of this paper is to explore how value-based management is perceived, implemented, and utilized in leading automotive corporations in Germany, and to examine factors that influence the decision to utilize it. The data was gained by using in-depth interviews with financial managers of German automotive corporation to study their opinions of and experiences with value-based management systems and metrics. The findings of the empirical study and primary research shows the problems of value-based management implementation in failing to achieve the right balance between all actors of agency conflict.
Keywords: G32; M21; 330; value-based management; shareholder-value; performance measurement; technique